If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -8 = -7 + x Combine like terms: -4 + -8 = -12 -12 = -7 + x Solving -12 = -7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -12 + -1x = -7 + x + -1x Combine like terms: x + -1x = 0 -12 + -1x = -7 + 0 -12 + -1x = -7 Add '12' to each side of the equation. -12 + 12 + -1x = -7 + 12 Combine like terms: -12 + 12 = 0 0 + -1x = -7 + 12 -1x = -7 + 12 Combine like terms: -7 + 12 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| -4y-10=6y+20 | | -4-8=-7 | | 19-42=3(x-2)-8 | | -2+9=14x-3-13x | | -5c+2=-18 | | -5(x+1)-11=21+3 | | 12(x-3)=-3-9 | | -2+5x=-32 | | 3x^3-9x^2+8x-7=2 | | 3(5y-4)=9y | | 6-x=20 | | -117=2(1-6p)-5p | | 5(5c-1)-4=21c+3 | | -(-9x-9y+4)= | | 3.5x=21 | | 4y^2-25x^2=100 | | 144=16t^2 | | 5=p+3 | | .3x+1.8=8 | | 3a-8a= | | 15x-2y=10 | | 5-.5x-3=4 | | 43y=6(7y-2) | | 6y=5(y+3) | | (x-3)(2x+3)=0 | | 5x^2=75 | | -2x-3-x=-3(-2x+7) | | 5x^2+25=100 | | 3(2x-3)=7 | | x^2+36=11 | | 2x^2+25=25 | | 2x^2-25=25 |